Pencegahan Stunting Menggunakan Metode Observasi dan Pendampingan di Desa Laboy Jaya Kecamatan Bangkinang, Kabupaten Kampar, Provinsi Riau - Roni Salambue; Annisa Devia Rahman; Bunga Ariski; Evan Albert Hubertus Samosir; Fara Pricyla; Felix Dwi Artha Pakpahan; Herol Govand Nesvagan Sigalingging; Inggyu Muria Br. Hasibuan; Ismi Sifa Adila; Valentina Br. Pakpahan; Zikri Alhadi (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake over a long period of time, which causes future problems in achieving optimal physical and cognitive development. The problem of stunting is a nutritional problem faced by the world, especially in poor and developing countries including Indonesia.  This activity was carried out in Laboy Jaya Village, Bangkinang District, Kampar, Riau. This activity begins with a theoretical explanation of stunting prevention about the factors that cause stunting and efforts to prevent and treat stunting itself. The result of this activity is that the Laboy Jaya Village community, especially mothers, can be more familiar with the dangers of stunting and can be prevented.